Kynurenine and depressive symptoms in a poststroke population - Bensimon K (Dove Medical Press, 2014)
Kira Bensimon,1,2 Nathan Herrmann,1,2,4 Walter Swardfager,1–4 Hao Yi,1 Sandra E Black,1–4 Fu-Qiang Gao,1,4 Abraham Snaiderman,2,3 Krista L Lanctôt1–4 1Sunnybrook Research Institute, Toronto, ON, Canada; 2Faculty of Medicine, University of Toronto, Toronto, ON, Canada; 3Toronto Rehabilitations Institute,Toronto, ON, Canada; 4Canadian Partnership for Stroke Recovery, Heart and Stroke Foundation, Ottawa, ON Canada Background and purpose: Depression is a commonly occurring and persistent sequel of stroke affecting approximately 29% of patients. An immunological hypothesis has been put forward, and synthesis of kynurenine from tryptophan has been proposed to link inflammatory activity with neurotoxicity and neurotransmitter dysfunction. This study assessed the relationship between peripheral blood kynurenine and poststroke depressive symptoms.Patients and methods: This was a multisite cross-sectional observational cohort study of patients with ischemic stroke. Depressive symptoms were assessed using the Center for Epidemiological Studies Depression (CES-D) scale and divided into high, medium, and low depressive symptom tertiles. Concentrations of kynurenine and tryptophan were assayed from fasting serum samples, and the kynurenine/tryptophan ratio was compared between tertiles. Serum cytokine concentrations were assayed in a subgroup of patients, and the ratio of proinflammatory (IL-6, IL-18, IFNγ, TNF, IL-1β) to anti-inflammatory (IL-10) cytokines compared.NLM identifier: NCT00254020.Results: In these patients (n=86, 52.3% male, mean age 71.7±14.2 years), there were no differences in kynurenine/tryptophan ratios between CES-D scale tertiles (F2,76=0.04, P=0.96) controlling for relevant covariates. For cytokines (n=53), serum IL-1β concentrations (F2,52=3.55, P=0.037) and serum ratios of IL-18/IL-10 (F2,52=3.30, P=0.046), IFNγ/IL-10 (F2,52=4.02, P=0.025), and IL-1ß/IL-10 (F2,52=4.34, P=0.019) were elevated in the middle CES-D tertile. Post hoc analyses suggested that serum ratios of IL-18/IL-10 (ρ=0.28, P=0.04), and IL-1ß/IL-10 (ρ=0.43, P=0.001), as well as IL-1ß (ρ=0.29, P=0.04), were significantly associated with fatigue.Conclusion: Peripheral kynurenine/tryptophan ratios were not associated with depressive symptoms in a poststroke population. However, in exploratory analyses a proinflammatory bias was identified specifically in patients with mild depressive symptoms and associated with poststroke fatigue, suggesting an avenue for future research. Keywords: kynurenine, tryptophan, cytokine, inflammation, stroke, depression